2007
DOI: 10.1029/2007je002894
|View full text |Cite
|
Sign up to set email alerts
|

Modeling impact cratering in layered surfaces

Abstract: [1] Impact craters are potentially powerful tools for probing large-scale structure beneath planetary surfaces. However, the details of how target structure affects the impact cratering process and final crater forms remain poorly understood. Here, we present a study of cratering in layered surfaces using numerical simulations. We implement the rheologic model for geologic materials described by Collins et al. (2004) into the shock physics code CTH; this model includes pressure, temperature, and damage effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 67 publications
7
104
0
Order By: Relevance
“…There are, however, a variety of impact damage studies upon which we can draw size estimates. Senft and Stewart (2007) used a shock physics code to reproduce final crater shapes and damage zones from laboratory to planetary scales. They found that the depth to the base of the damage zone is~1/4 the final crater diameter, a result in qualitative agreement with data from terrestrial craters (Ahrens et al, 2001).…”
Section: Influence Of the Extent Of The Apollodorus Impact Damage Zonementioning
confidence: 99%
“…There are, however, a variety of impact damage studies upon which we can draw size estimates. Senft and Stewart (2007) used a shock physics code to reproduce final crater shapes and damage zones from laboratory to planetary scales. They found that the depth to the base of the damage zone is~1/4 the final crater diameter, a result in qualitative agreement with data from terrestrial craters (Ahrens et al, 2001).…”
Section: Influence Of the Extent Of The Apollodorus Impact Damage Zonementioning
confidence: 99%
“…In case of a hypervelocity impact of a small steel sphere onto a target, the main damage is due to tensile and shear strength. Senft and Stewart [8] compared results from simulations with both tensile and shear damage as well as with tensile damage only. It showed tensile loading is mainly responsible for the damaging process.…”
Section: Porous Modelmentioning
confidence: 99%
“…Metals have been widely studied, both experimentally [6] and through the use of numerical hydrocodes [7]. Some brittle materials have also been included in HVI studies, such as geophysical materials [8], and silica glass that covers solar arrays or can be used as transparent windows [9]. Experiments and hydrodynamic simulations have emphasized their difference with ductile metals [10].…”
Section: Introductionmentioning
confidence: 99%
“…A second seismic experiment carried out in 2005 improved the resolution of these seismic models significantly and allowed better constraints on the crater asymmetries and the central uplift [Vermeesch and Morgan, 2008]. Numerical models for the formation of large complex impact craters and multiring basins all show an upward movement within the center of the crater during collapse [e.g., Grieve et al, 1981;Collins et al, 2002;Wünnemann et al, 2005;Senft and Stewart, 2007]. When excavation has ceased, the uplifted rim collapses inward and downward to form a terrace zone, and the uplifted central zone collapses downward and outward to form a peak ring [e.g., Collins et al, 2002].…”
Section: Introductionmentioning
confidence: 99%